Clinical and basic research advances on Jinlong capsule for the prevention and treatment of liver cancer - Lv, Liyuan; Ren, Simeng; Zhang, Zunyi; Lin, Hongsheng; Liu, Jie (Frontiers in Pharmacology, 2025)
IntroductionPrimary liver cancer, characterized by an insidious onset, rapid progression, high degree of heterogeneity, difficulties in treatment, and a short survival time, poses a significant threat to human health. Jinlong capsule (JLC), an original drug developed in China, is a Chinese patent medicine used to treat liver cancer. Research has demonstrated the antitumor effects of JLC, attributed to its unique preparation process. When used in combination with modern treatment methods, JLC helps in preventing and treating liver cancer recurrence and metastasis, prolonging patient survival, increasing the tumor objective response rate, alleviating gastrointestinal adverse reactions, enhancing survival quality, regulating immune functions of the body, relieving clinical symptoms, and improving patient safety. This study provides a review of clinical and basic research results on JLC.MethodsWe performed literature searches in the Cochrane Library, Embase, PubMed, OVID Scopus, China Biology Medicine, China National Knowledge Infrastructure, VIP, and Wanfang databases for articles published from database inception to December 2023.ResultsBasic research has revealed that the effects of JLC include the inhibition of tumor growth in vivo and in vitro and immune modulation. The possible mechanisms include inhibiting tumor cell proliferation, promoting tumor cell apoptosis, inhibiting angiogenesis, and modulating cellular immunity.DiscussionBy attuning to the complex biological characteristics of liver cancer, harnessing the unique and unconventional advantages of traditional Chinese medicine, and focusing on clinical needs, we propose directions for future evidence-based research on using JLC in the prevention and treatment of liver cancer. This will contribute to the development of precision synergistic strategies that combine traditional Chinese medicine and modern medicine treatment methods.